2022
DOI: 10.28945/4996
|View full text |Cite
|
Sign up to set email alerts
|

Teacher-Student Interaction in Distance Learning in Emergency Situations

Abstract: Aim/Purpose : The goal of this study was to examine which of the types of teacher-student interactions found in previous studies by Kang (2009) and Kang and Im (2013) during distance learning in routine situations, were also found in times of emergency, specifically during the COVID-19 pandemic, and whether these interactions differed between students with regard to the extent and nature of each type of interaction. Background: Teacher-student interactions during learning in general and particularly in distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…One study enumerated the main challenges in terms of educational, organizational, ethical, technical, supportive and managerial aspects, and particularly, in terms of evaluation and communication [22]. Sason et al (2022) reported that during the COVID-19 pandemic, students insisted that they needed to interact with their teachers. From the learners' perspective, the most common form of interaction was e-mailmediated educational Interaction.…”
Section: Quality Of Interpersonal Interaction In E-learningmentioning
confidence: 99%
See 2 more Smart Citations
“…One study enumerated the main challenges in terms of educational, organizational, ethical, technical, supportive and managerial aspects, and particularly, in terms of evaluation and communication [22]. Sason et al (2022) reported that during the COVID-19 pandemic, students insisted that they needed to interact with their teachers. From the learners' perspective, the most common form of interaction was e-mailmediated educational Interaction.…”
Section: Quality Of Interpersonal Interaction In E-learningmentioning
confidence: 99%
“…Being knowledgeable of communication weaknesses in online environments can help educators to develop appropriate materials [ 2 ]. Given the role of interaction between the teacher and the learner and, and given the importance of meeting the needs of different students, in distance teaching, teachers should find new ways to communicate with their students and use new communication methods appropriate for synchronous and asynchronous learning environments [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have presented that in e-learning environment, the learning schemes and the way lectures are delivered are not adequately adapted to accommodate the large number of learners with different perceptions. For this reason, learning in a virtual environment leads to problems that must be taken into account [2]. The main goal of an educational website is to provide a high quality educational VOLUME 11, 2023 platform, and the most important thing is that it should lead to valuable functions for academic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…In response, teachers continually modified curriculum, learning environments, and assessments, to sustain student access through ongoing adaption of practice (de Bruin & Merrick, 2023). Changes in the teaching process saw an elevated level of student responsibility emerge, with increased application of planning and strategy use to facilitate task completion (Sason & Kellerman, 2022). The pandemic fostered pedagogies "that engage student thinking and collaboration with each other in online learning activity" (de Bruin & Merrick, 2023, p. 155).…”
Section: Introductionmentioning
confidence: 99%